RESTORATIVE JUSTICE IN THE SETTLEMENT OF DEFAMATION CASES IN THE ITE LAW: RESTORATIVE JUSTICE DALAM PENYELESAIAN KASUS PENCEMARAN NAMA BAIK DALAM UU ITE - Yana, Tri (LPPM UPMI, 2023)
Indonesia is a constitutional state, in line with the wording of Article 1(3) of the 1945 Constitution of the Republic of Indonesia. Therefore, all aspects of social life are protected by the state constitution. The rule of law includes the constitutional rights of citizens, one of which is the right to freedom of association, assembly and expression of opinion, as set forth in Article 28e(3) of the 1945 Constitution. One of the basic rights enshrined in the Constitution is the right to freedom of expression in public. In giving public comments, you can use electronic media regulated in Law Number 19 of 2016 concerning Information and Electronic Transactions. The law covers criminal acts in the fields of technology and electronic transactions, and regulates the delivery of opinions in electronic media. As a result, the expression of opinions through electronic media is subject to legal restrictions.